Utilization of Trichoderma sp. and compost to increase nitrogen in specific soil types as planting media - Maroeto, Maroeto; Wijayanti, Fitri; Lestari, Safira Rizka; Maghfiroh, Ainur Risma Miftakhul (Jurnal Ilmu Pertanian, 2025)
Nitrogen deficiency dramatically affects plant growth, development, and productivity. This study aims to determine the utilization of Trichoderma sp. and compost in increasing the nitrogen content of several types of soil used as planting media. The research was conducted using an experimental method arranged in a completely randomized design (CRD) factorial pattern. The first factor is the soil types, namely Alfisol, Inceptisol, and Vertisol. The second factor is dose of compost consisting of 4 levels, namely K1 (0 tons ha-1 or no compost), K2 (10 tons ha-1), K3 (20 tons ha-1), and K4 (30 tons ha-1). The third factor is the concentration of Trichoderma sp., which consists of 4 levels, namely T1 (0 CFU ml-1), T2 (106 CFU ml-1), T3 (108 CFU ml-1), and T4 (1010 CFU ml-1). Results showed that the combination of compost and Trichoderma sp. had a natural effect on increasing the N content of each soil type. N-total content from highest to lowest was found in soil types such as Inceptisol (0.384%), Alfisol (0.243%), and Vertisol (0.230%). Combining compost and Trichoderma sp. increases sustainable nitrogen availability and is more environmentally friendly.